(untitled) (Research, Society and Development, 2022)
Social networks on the Internet are becoming a new space-time for learning and sharing content on different topics. In this experience report, we use Instagram as a pedagogical means for scientific dissemination and academic training of future nutritionists. Thus, this work aimed to analyze how the creation and management of a Studygram on EAN, developed by nutritionists in training, participants in an extension project, contributed to the improvement of the undergraduate and the popularization of healthy and balanced eating habits. The results reveal that the process of research, organization and production of content to be shared in Studygrams required efforts such as adapting the technical language, so that the information became clearer and more objective; customized and standardized aesthetics; monitoring of scientific news and posting metrics; formation of partnerships with similar interest profiles, among others. The dynamics of construction and management of Studygrams during a university extension project was enriching for the members as it favored the expansion of knowledge in nutrition and the development of skills and competences for the professional performance of the nutritionist in the virtual environment. In addition, we defend, from our experiences, that social networks such as Instagram can be useful tools for Food and Nutrition Education, as they constitute an open, interactive and customizable environment, favoring the development of health promotion actions.